2017
DOI: 10.1093/ajcp/aqx035
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Indirect- and Direct-Acting Anticoagulants on Lupus Anticoagulant Assays

Abstract: Results of LAC testing performed while patients are receiving anticoagulant therapies should be interpreted with caution to avoid misdiagnosing patients with the antiphospholipid syndrome and potentially committing them to long-term anticoagulation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 26 publications
5
27
0
Order By: Relevance
“…This effect of emicizumab on DRVVT is much smaller than the effect of direct oral anticoagulants on this assay. 7 The mechanism of DRVVT prolongation is likely due to a weak steric interference with coagulation reactions in which FXa is generated, due to the binding of FX by emicizumab. 8 The lack of effect of emicizumab on TVT was expected, as emicizumab acts further upstream in the coagulation cascade.…”
Section: Dear Editorsmentioning
confidence: 99%
“…This effect of emicizumab on DRVVT is much smaller than the effect of direct oral anticoagulants on this assay. 7 The mechanism of DRVVT prolongation is likely due to a weak steric interference with coagulation reactions in which FXa is generated, due to the binding of FX by emicizumab. 8 The lack of effect of emicizumab on TVT was expected, as emicizumab acts further upstream in the coagulation cascade.…”
Section: Dear Editorsmentioning
confidence: 99%
“…Tests for LA detection should include screening, mixing and confirmation steps performed with at least two different methodologies, with only one result required to be positive [19,35]. Many studies have reported DOAC interference with tests for LA, leading to false-positive and unreliable results [36][37][38][39]. Dabigatran and apixaban interfere with both activated partial thromboplastin time (aPTT) based and dilute Russell viper venom time (dRVVT) based tests [40][41][42][43].…”
Section: Laboratory Monitoring Of Anticoagulation In Patients Receivimentioning
confidence: 99%
“…This highly selected patient population explains the high incidence of thrombophilic factors reported in the 50 patients finally included in this study (e.g., 76% lupus anticoagulant in the study group (n = 50) compared to 25.2% in the patient population screened (n = 151) and listed for liver transplantation at Menoufia University). We are aware that oral anticoagulants - vitamin K antagonists as well as direct oral anticoagulants (DOACs) - and heparin can interfere with lupus anticoagulant assays [32,33]. This was one reason to exclude liver transplant recipients with oral anticoagulation from the study.…”
Section: Discussionmentioning
confidence: 99%